Universities, the public good and professional education in the UK - East, Linda; Stokes, Rebecca; Walker, Melanie (Taylor & Francis, 2013)
In times of economic uncertainty, questions of the purpose and value of higher education come to the fore. Such questions have particular relevance when directed towards the preparation of professionally qualified graduates who might be expected to contribute to the public good. However, definitions of the public good are contested and the role of higher education is unclear. This interview-based study contributes to the debate by taking a professional capabilities index (PCI) generated in South Africa and interrogating it in the UK context. The PCI is oriented towards poverty reduction and is grounded in the human development and capabilities approach, an agenda to which UK respondents were broadly sympathetic although with differences in emphasis. This article argues that, if we are to move beyond a narrow economic understanding of the public good and a purely instrumental understanding of graduate ‘attributes’, the human development and capabilities approach has much to offer.